Papiri della Società Italiana. Vol. XVI Volume sedicesimo (PSI XVI) - Messeri, Gabriella; Bastianini, Guido; MALTOMINI, FRANCESCA (Edizioni dell'Istituto Papirologico «G. Vitelli», 2013)
This volume is the 16th of the PSI series (started by Girolamo Vitelli in 1912) and contains the edition of 79 texts written in Greek on papyri or other materials (wood, parchment), coming from Egypt and kept at the Papyrological Institute «G. Vitelli». There are both fragments of famous Ancient Greek authors (Homer, Hesiod, Herodotus, Thucydides, Xenophon, Isocrates, Demosthenes, Plutarch; the Septuagint, Cyril of Alexandria, the Physiologist), as well as fragments of unknown works: among others, a grammar text on the Ionian dialect and a doxographic fragment on Aristotelian philosophy. Then, there are texts of documentary nature: petitions, tax receipts, registers, reports, private letters, testimony of the daily life in Egypt during Roman and Byzantine times.